Variational Modification of Žemočkin Contact Problems Solution Method - Mistrikova, Z.; Slozka, V. (Engineering Transactions, 1995)
The present paper deals with some contact problems. In the well-known Žemočkin method of solving the contact problem of two bodies (structure - elastic half-space), the condition of perfect contact (mutual displacements of two bodies equal zero) is fulfilled only in a chosen number of points. In a modification of the Žemočkin method presented by the authors, the reciprocity of displacements of two bodies is minimized by a functional of potential energy of deformation. Some numerical results concerning the problem of contact of a plate and an elastic half-space based on this solution are included.